Secondary structure model for bacterial 16S ribosomal RNA: phylogenetic, enzymatic and chemical evidence. - Woese, C R (1980)
We have derived a secondary structure model for 16S ribosomal RNA on the basis of comparative sequence analysis, chemical modification studies and nuclease susceptibility data. Nucleotide sequences of the E. coli and B. brevis 16S rRNA chains, and of RNAse T1 oligomer catalogs from 16S rRNAs of over 100 species of eubacteria were used for phylogenetic comparison. Chemical modification of G by glyoxal, A by m-chloroperbenzoic acid and C by bisulfite in naked 16S rRNA, and G by kethoxal in active and inactive 30S ribosomal subunits was taken as an indication of single stranded structure. Further support for the structure was obtained from susceptibility to RNases A and T1. These three approaches are in excellent agreement. The structure contains fifty helical elements organized into four major domains, in which 46 percent of the nucleotides of 16S rRNA are involved in base pairing. Phylogenetic comparison shows that highly conserved sequences are found principally in unpaired regions of the molecule. No knots are created by the structure.